2018
DOI: 10.1002/cctc.201801438
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Limitations of the Catalyst Design Space for Methanol Production from Methane

Abstract: Current efforts to overcome the challenges of direct methane to methanol processes have focused on designing heterogeneous catalysts that perform methane partial oxidation using cheap and abundant oxidants such as molecular oxygen and water. An evaluation of the thermodynamic limitations of methanol production with the use of these oxidants is required to understand the maximum possible conversion and selectivity for a given feed composition and temperature. When O2 is present, the formation of the most thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 37 publications
(91 reference statements)
0
14
0
Order By: Relevance
“…Based on the observation that surface methoxy/alkyl groups were formed during methane activation and a thermodynamic analysis that indicated that an oxidant like O 2 is needed for methanol production, [1c] we hypothesized that the direct conversion from methane to methanol can be achieved by feeding steam and oxygen together with methane. Under the reaction conditions reported, continuous direct conversion from methane to methanol was achieved for all catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the observation that surface methoxy/alkyl groups were formed during methane activation and a thermodynamic analysis that indicated that an oxidant like O 2 is needed for methanol production, [1c] we hypothesized that the direct conversion from methane to methanol can be achieved by feeding steam and oxygen together with methane. Under the reaction conditions reported, continuous direct conversion from methane to methanol was achieved for all catalysts.…”
Section: Discussionmentioning
confidence: 99%
“…[28] There is a variety of other recent literature showing methane partial oxidation to methanol, syngas, or other products. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Our work on the partial oxidation of methane has focused on the search for processes efficient under less acidic environments, in particular trifluoroacetic acid (TFAH). [44] For instance, we have characterized a number of rhodium complexes with C-H activation ability in TFAH.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Natural gas has been exploited from shale gas recently, the amount of which is estimated to be more than 7299 trillion cubic feet. [13][14][15][16][17] Methane also could be naturally generated from biosystems as marsh gas through the anaerobic digestion of crops, wastes and residues. [18,19] Human activities, such as coal mining, natural gas or petroleum drilling and breakdown of garbage in landfills, significantly contribute to the release of CH 4 .…”
Section: Introductionmentioning
confidence: 99%